Study Regarding Accounting Treatment of Green Certificates in Romania - OCNEAN, Monica (International Journal of Scientific Research and Management (IJSRM), 2021)
Accounting regulations approved through Order 1802/2014 makes remarks regarding the reflection of green certificates in accounting.      Green certificates are titles that attest the production of a quantity of electrical energy from renewable sources. These can be traded distinctly from the amount of electrical energy that they represent. A.N.R.E. (National Agency of Energy Regulation) rewards producers of renewable electricity to benefit the promotion of sustainable energy through green certificates. Electricity providers and some producers are required to purchase a number of green certificates on a quarterly basis. They are then required to transmit to the National Agency of Energy Regulation, in the specified format and by the deadline set by them, the quantities of electrical energy for which they need to purchase green certificates, in conformity with law 220/2008. The cost of green certificates is billed separately from the price of electric energy inaccounting tratament the invoice sent to the final customers. Providers or producers that do not meet the yearly quota must pay the value of green certificates not acquired in said timespan. According to the ministry’s of public finance Order 1802/2014, producers of renewable energy, that benefit from green certificates provided by the transport and system operator must register the green certificates received into their accountings using specific accounting accounts